Analisis Potensi dan Strategi Pengembangan Ekowisata Arung Jeram Sungai Asahan Berbasis ECOS dan Keberlanjutan Sosial-Ekonomi - Rahmad Kurnia Abdik Nasution; M. Halfi Indra Syahputra (Jurnal Visi Manajemen, 2024)
The Asahan River in North Sumatra holds significant potential as an ecotourism destination for whitewater rafting, featuring Class IV-V+ rapids that attract both domestic and international tourists. This study aims to analyze the potential and development strategies for ecotourism in the Asahan River using the Ecotourism Opportunity Spectrum (ECOS) approach with the addition of a socio-economic sustainability variable. This approach evaluates seven key components: accessibility, attractions, infrastructure, social interaction, skill and knowledge levels, related resources, and visitor impact. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using a descriptive qualitative method. The results indicate that the Asahan River is classified as an Eco Specialist, with high natural appeal but requiring improvements in accessibility and community participation. Socio-economic sustainability assessments reveal that economic benefits are not evenly distributed, and local community involvement in tourism management remains low. Proposed strategies include improving infrastructure, training local communities, digital promotion, and strengthening stakeholder collaboration to establish a sustainable tourism destination.